Evaluating end-user satisfaction with an e-government service electronic labor exchange (ELX) - Zulridah Mohd Noor; Hasmiah Kasimin; Aini Aman; Noraidah Sahari (Penerbit Universiti Kebangsaan Malaysia, 2011)
A major domain of e-government research has been the examination of information delivery to citizens. These services involve communications and transactions between government, at various levels, and citizens The rise of these services has led to a concurrent need to develop models of citizen satisfaction with e-governmental services.This research aims to contribute to this need by devising an ELX consumer satisfaction index (ELXCSI) model and using it to evaluate citizen satisfaction with e-government electronic labor exchange (ELX) service delivery in Malaysia.This paper presents result of a statistical analysis of an end-user survey conducted in 2009 to evaluate user satisfaction with ELX service. Using structural equation modeling, a highly statiscally significant goodness-off-fit was found for the model, which included 15 measures capturing three performance contructs (utility, efficiency,customization) as affecting satisfaction. The calculated ELXCSI of 66 indicates that more effort should be carried out by government to improve performance measurements in order to increase satisfaction among end-users of ELX service in Malaysia.